Comparison of 3D Coral Photogrammetry and Coral Video Transect for Coral Lifeform Analysis Using Low-cost Underwater Action Camera - Zuhairi Bin Ahmad; Muhammad Idzham Helmi Bin Mohd Jinah; Shahbudin Bin Saad (Universitas Gadjah Mada, 2020)
This research analysed the use of 3D Coral Photogrammetry (CP) and Coral Video Transect (CVT) images collected from SCUBA divers using a low-cost underwater action camera to examine the coral lifeform. A comparison was made between data sets obtained using both methods on nine transects with different coral lifeform compositions and percentage cover within an area of 4 × 7 m. The comparison of the statistical analysis for CPCe revealed that there were no significant differences (p < 0.05) between CP and CVT photos where dead corals (p = 0.006), sand (p = 0.011), and unknown (p = 0.002) are present. Additionally, the coral value (p = 0.131) between CP and CVT was not significant. CP was capable of producing prominent branching, massive, and plate coral morphology results. This suggests that survey methods using low-cost action cameras for 3D Coral Photogrammetry would yield appropriate results in terms of coral lifeform detection. Hypothetically, by improving camera quality, it will yield a higher accuracy of 3D coral images that are suitable for use in scientific research and management. Other benefits of using CP include the possibilities for future studies with 3D coral surveys using remotely operated vehicles, less field time, and 3D coral seabed information.